Commensalism of Fusobacterium nucleatum - The dilemma - Sangeeta Nayak; Nishmitha D. Shetty; Deepa G. Kamath (Journal of Indian Society of Periodontology)
Fusobacterium nucleatum is a Gram-negative, anaerobic bacterium that serves as a periodontal pathogen and plays a key role in linking Gram-positive and Gram-negative bacteria within the periodontal biofilm. It was shown that Fusobacterium produces significant amounts of butyric acid, which is a great source of energy for anti-inflammatory cells. On the other hand, it is associated with the destruction of periodontal structures. This bacterium can enter the blood circulation as a result of periodontal infection. It could cause numerous conditions such as halitosis, dental pulp infection, oral cancer, and systemic diseases. The present review discusses the virulence mechanisms involved in the diseases, with emphasis on its colonization, systemic dissemination, and induction of host inflammatory and tumorigenic responses. This would motivate future research on the role of this bacterium on periodontal pathology as well as its influence on the evolution of systemic diseases.